English and Indonesian Singular Forms: A Case of Nouns - Masagus Sulaiman; Masagus Firdaus (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
This study is aimed at finding out the similarities, dissimilarities, and possible learning difficulties faced by students learning English and Indonesian singular forms as well as its contribution to TEFL. The researchers used a qualitative research design. The documentation technique was used to collect the data. To analyze the data, the researchers used descriptive analysis. The results showed that there were four similarities and two dissimilarities between English and Indonesian singular forms. The four similarities were in indefinite article, definite article, quantitative adjective, and units of measurement. While the two dissimilarities were in the definite article and definite article. The possible learning difficulties faced by students learning English and Indonesian singular forms were that they were not very familiar with grammar rules and it made them perplexed and created mistakes when writing and speaking. The contribution was as teaching guidance that assists English teachers to create a better teaching Grammar design on singular forms in terms of countable and non-countable nouns.